THE IMPACT OF ADVERSE CHILDHOOD EXPERIENCES ON MENTAL HEALTH AND INVOLVEMENT IN ABUSIVE RELATIONSHIPS IN ADULTHOOD - Saida Elkhan gyzy HUSEYNOVA (Psychology Travelogs, 2026)
Adverse childhood experiences (ACEs) constitute key etiological risk factors for the development of mental disorders and maladaptive interpersonal behavior. This study examines the relationship between the level of ACEs and the likelihood of future involvement in abusive relationships, alongside assessing accompanying indicators of anxiety, depression, and post-traumatic stress symptoms. The empirical research utilized a comprehensive psychodiagnostic battery, including the Adverse Childhood Experiences Questionnaire (ACE), General Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire (PHQ-9), PTSD Checklist (PTCI), and Profile of Psychological Abuse Questionnaire. The sample comprised 214 respondents stratified into clinical and control groups. Data analysis involved comparative, correlational, and multiple regression methods. The study establishes a differentiated mapping of specific childhood traumas against adult psychopathology. Emotional abuse and neglect uniquely predict adult depression and anxiety. Material deprivation demonstrates a selective significant correlation with specific post-traumatic cognitions, including internalized self-blame and rigid negative beliefs about the self and the world. Childhood sexual abuse is verified as a universal catalyst inducing total mental destabilization across all measured clinical indicators. Witnessing interparental violence and parental mental illness selectively prime individuals for elevated generalized anxiety. Adults with a history of abusive relationships demonstrate significantly higher cumulative ACE scores and comorbid trauma symptoms. Early psychic trauma undermines the psychological defense system, fixing the individual in a vulnerable relational position. Effective clinical rehabilitation requires a paradigm shift from standard educational programs toward prolonged, trauma-informed psychotherapeutic interventions. Clinicians must assess the underlying childhood traumatic substrate to prevent potential relapses of adult re-victimization.